From App Cues to Trust: A Stimulus–Organism–Response Study of Engagement and Continuance Intention in Indonesian Food Ordering Apps - Endah Budiarti; Tri Andjarwati; Enni Sustiyatik (Universitas Negeri Semarang, 2026)
This study investigates the influence of design, performance, and user reviews on consumer engagement and continuance intention, with situational factors serving as a moderating variable in the context of food ordering applications. To explain consumer engagement and continuance intention as behavioral outcomes shaped by app-related cues and internal user evaluations, this study draws on consumer behavior theory. The Stimulus–Organism–Response (SOR) model is used as the conceptual framework. Empirical study using quantitative cross-sectional technique is conducted on 338 respondents from nine major cities in Indonesia. PLS-SEM is used to examine data. The findings show that design, performance, and user reviews significantly influence user engagement, with app performance having the strongest effect. Engagement significantly predicts continuance intention, while situational factors moderate this relationship. Managerially, food-ordering platforms should focus on app stability and speed, enhance trust signals, manage user reviews strategically, and design situational features that address delivery uncertainty and time pressure.